Effects of vitamin D receptor gene polymorphisms on the prognosis of COVID‐19. (25th December 2021) - Apaydin, Tugce; Polat, Hamza; Dincer Yazan, Ceyda; Ilgin, Can; Elbasan, Onur; Dashdamirova, Saida; Bayram, Feyza; Tukenmez Tigen, Elif; Unlu, Ozan; Tekin, Ahmet F.; Arslan, Ebru; Yilmaz, Ipek; et al.
Abstract: Purpose: Vitamin D deficiency has emerged as another potential risk factor for coronavirus disease (COVID‐19) due to the immunomodulatory effects of 25 hydroxyvitamin D [25 (OH)D]. Vitamin D receptor (VDR) gene polymorphisms such as Fok I, Bsm I, Apa I, and Taq I are also associated with different courses of viral infections. This study aimed to evaluate the association between the VDR gene polymorphism at Fok I, Taq I, Bsm I, and Apa I genotypes and the prognosis of COVID‐19 in respect to vitamin D deficiency. Methods: Two‐hundred ninety‐seven patients with COVID‐19 were enrolled. Serum 25 (OH)D levels were measured. Four variant regions of the VDR gene, FokI, BsmI, ApaI, and TaqI were determined. Results: Eighty‐three percent of subjects had vitamin D deficiency, and 40.7% of the whole group had severe deficiency. Median 25 (OH)D level was 11.97 ng/ml. Vitamin D levels were not related to inflammatory markers, disease severity, admission to intensive care unit (ICU), and mortality. While disease severity was related to Fok I Ff genotype, it was Taq TT genotype for ICU admission. Moreover, the ApaI aa genotype was common among the patients who were died. None of the deceased subjects had the Fok I FF genotype. Conclusion: 25 (OH)D levels were not related to the severity and mortality of COVID‐19. VDR gene polymorphisms are independently associated with the severity of COVID‐19 and the survival of patients.